2003
DOI: 10.1161/01.atv.0000069847.72001.e8
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Imaging of the Dynamics and Secretory Behavior of Weibel-Palade Bodies

Abstract: Objective-Weibel-Palade bodies (WPBs) are specialized secretory granules found in endothelial cells. These vesicles store hormones, enzymes, and receptors and exhibit regulated exocytosis on cellular stimulation. Here we have directly visualized intracellular trafficking and the secretory behavior of WPBs in living cells by using a hybrid protein consisting of von Willebrand factor (vWF), a prominent WPB constituent, and green fluorescent protein (GFP). Methods and Results-Immunofluorescence microscopy demonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
85
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(94 citation statements)
references
References 39 publications
(25 reference statements)
8
85
0
1
Order By: Relevance
“…For rescue experiments, a siRNA-insensitive mutant (anxA8i) was generated by introducing seven silent mutations into the siRNA-targeted region of the anxA8 cDNA. VWF-EGFP containing an internal GFP replacing the A2 domain of VWF 35 was a kind gift from Jan Voorberg (Sanquin Research, Amsterdam).…”
Section: Discussionmentioning
confidence: 99%
“…For rescue experiments, a siRNA-insensitive mutant (anxA8i) was generated by introducing seven silent mutations into the siRNA-targeted region of the anxA8 cDNA. VWF-EGFP containing an internal GFP replacing the A2 domain of VWF 35 was a kind gift from Jan Voorberg (Sanquin Research, Amsterdam).…”
Section: Discussionmentioning
confidence: 99%
“…Confluent cells were fixed with PBS/3.7% paraformaldehyde (PFA) and prepared for immunofluorescence analysis as described. 30 Monoclonal antibody CLB-Rag20 29 was used to visualize VWF. Rabbit polyclonal antibody anti-human CD62-P (BD PharMingen, San Diego, CA, USA) was used to visualize P-selectin.…”
Section: Immunofluorescence Microscopymentioning
confidence: 99%
“…This suggests that WPBs could manoeuvre within cells by sharply bending at hinges rather than curling around obstacles. To observe bending WPBs in live cells over time, we took advantage of a VWF construct where the A2 domain was replaced by GFP (Romani de Wit et al, 2003). Expression of this construct in HUVECs revealed that most bending WPBs had only one break point or hinge.…”
Section: Wpb Movement Within Cellsmentioning
confidence: 99%